Are South African linefishes recovering and what makes them prone to overexploitation? - Haupt, M; Winker, H; Parker, D; Kerwath, SE (African journal of marine science, 2020)
Managing coastal fisheries is challenging as the status of many fish stocks caught in these fisheries remains unknown. In the South African linefishery, regular comprehensive assessments of the status of most linefish stocks are unattainable owing to a scarcity of reliable long-term data. Length-based analysis remains the only option to determine stock status in the form of spawning potential ratio (SPR), as life-history information and representative length samples are available for many linefish species. Although per-recruit models are susceptible to bias due to violation of the steady-state assumption, the SPR has been shown to be robust for long-lived species under reasonably consistent fishing mortality. In this study we used observer-collected length-frequency data from two time-periods 20 years apart (1988-1990 and 2008-2010), before and after management regulations were implemented, in combination with life-history information, to estimate the SPRs for 17 linefish species. We then correlated the recent stock-status estimates to species-specific life-history traits to identify length-based indicators of susceptibility to exploitation. Most species showed improvements in SPR between the periods, caused mainly by decreases in fishing mortality (F) and also increases in length-at-first-capture (L c ). The ratio between L c and asymptotic length (L c /L ∞ ), and the ratio between L c and optimum length (L c /L opt ), had significant relationships with SPR. We suggest that length-based indicators could be used to classify risk to overfishing in data-poor fisheries for medium- to long-lived species when time-series data are not attainable, but where representative size samples and adequate life-history information exist.